Pengaruh Content Marketing Brand di TikTok dan Persepsi Harga Terhadap Impulse Buying Produk Roti - Murfianingsih, Novia; Nurchayati, Nurchayati; Sulistiyani, Sulistiyani; Widayati, Tri (Forum Kerjasama Pendidikan Tinggi, 2026)
The development of social media has driven changes in consumer behavior, particularly in spontaneous purchasing decisions (impulse buying), along with the increasing utilization of digital platforms as marketing media. TikTok has become one of the platforms widely used by brands to deliver engaging and persuasive marketing content. This study aims to analyze the influence of content marketing and price perception on consumer impulse buying of Roti'O products in Semarang City. This study employs a quantitative approach with associative research design. The sampling technique used was purposive sampling with criteria of TikTok users who have viewed Roti'O content and made product purchases. Data were collected through questionnaires and analyzed using multiple linear regression analysis with SPSS software. The results show that simultaneously, content marketing and price perception have a positive and significant effect on impulse buying with an F value of 10.325 (p = 0.000) and an Adjusted R² value of 0.159, indicating that 15.9% of the variation in impulse buying can be explained by both variables. Partially, content marketing has a positive and significant effect on impulse buying (t = 2.795; p = 0.006), where relevant, informative, valuable, easy-to-understand, easily discoverable, and consistently presented content can attract attention and create emotional interest that encourages spontaneous purchases. Price perception also has a positive and significant effect on impulse buying (t = 2.086; p = 0.040), where prices perceived as affordable, aligned with product quality and benefits, and competitive can shape positive value perceptions in consumers' minds, thereby encouraging unplanned purchase decisions. The novelty of this study lies in the simultaneous examination of the influence of TikTok-based content marketing and price perception on impulse buying for food products, positioning TikTok as an interactive and emotional visual marketing medium to provide contextual understanding of the mechanisms underlying impulsive buying behavior formation in the digital marketing era. This study provides theoretical contributions to the development of digital marketing studies and practical contributions for business practitioners in designing effective content strategies and pricing to enhance consumer impulse buying.